RECONSTRUCTION OF MALAY TEACHING VALUES IN FOLKLORE OF RIAU PROVINCE BASED ON DIGITAL TECHNOLOGY - Anisa Putri, Meysi; Roziah (JURNAL KONFIKS, 2026)
This study aims to describe the Malay cultural values found in folk tales analyzed based on the concept of Tunjuk Ajar Melayu according to Tenas Effendy. The focus of the study includes religious values, hard work, responsibility, compassion, independence, self-awareness, generosity, sincerity, and gratitude. The method used is descriptive qualitative with content analysis techniques. The data consists of narrative quotations and character dialogues that contain Malay moral and cultural teachings, which are then analyzed by relating them to the principles of Tunjuk Ajar Melayu. The results of the study show that the characters in the stories display attitudes that are in line with the noble values of Malay society, such as working hard to earn a living, teaching selflessly, being responsible for the family, loving others, being generous, and being grateful for God's blessings. These values not only serve as guidelines for individual behavior, but also as the foundation for the formation of a civilized, religious, and noble society.